Dynamic Profitability Determinants in Chinese Banking Industry - Wan, Ruixuan (2017)
The purpose of this dissertation is to study the dynamic profitability determinants on the Chinese banking industry. Firstly, it is found that bank profitability could be significantly affected by the bank profit in the last year. Then, from the perspective of the internal determinants, it is found that the recurring earning power of the bank has significantly positive relationship with the bank profitability, the size of bank has significantly no impact on the bank profitability, the capital adequacy has positive relationship with the bank profitability, the liquidity of bank has negative relationship with the bank profitability, the expense management of the bank has negative relationship with the bank profitability. Lastly, from the perspective of the external determinants, it is found that both loan growth rate and GDP growth rate have positive relationship with bank profitability, and GDP growth rate is much more significant than the loan growth rate, which means GDP growth rate matters more than the credit cycle for the bank profitability in China. In addition, it is found that quadratic model could explain better and more precisely on the relationship between the house price change and the bank profitability, which is first positive and then negative relationship.